LONG-TERM RESULTS FROM THE SPYRAL HTN-ON MED TRIAL: RENAL DENERVATION INCREASES TIME IN BLOOD PRESSURE TARGET RANGE OVER 36 MONTHS. (June 2022) - Tsioufis, Konstantinos; Kandzari, David; Kario, Kazuomi; Townsend, Raymond; Mahfoud, Felix; Weber, Michael; Schmieder, Roland; Pocock, Stuart; Fahy, Martin; Bohm, Michael
Abstract : Objective: Six-month results from the SPYRAL HTN-ON MED pilot trial showed that patients with antihypertensive medications that underwent renal denervation (RDN) had a significantly greater reduction in 24-hr ambulatory and office systolic blood pressure (BP) from baseline compared to sham control. However, the effect of RDN on BP burden over time has not been established. Time in target range (TTR) analysis estimates the percent of time since procedure spent in a preferred systolic BP range as an indicator of BP control. An increase in TTR is associated with significantly lower risk of major cardiovascular events. In this analysis, we evaluate the long-term safety and efficacy of RDN in the SPYRAL HTN-ON MED pilot trial. Design and method: Eligible patients were enrolled in SPYRAL HTN-ON MED with an office systolic BP (OSBP) of 150 to < 180 mmHg, office diastolic BP > = 90 mm Hg, and a 24-hr mean ambulatory systolic BP (ASBP) of 140 to < 170 mmHg. Successive follow-up BP measures over 36 months were linearly interpolated to estimate TTR over time. BP target range was defined as 24-hr ASBP < = 140 mmHg and OSBP < = 140 mmHg. TTR was calculated for each patient as the proportion of time spent in the target BP range since the procedure, including the baseline BP measurement. At 24 months (RDN, n = 34; control, n = 17) there were fewer patients with follow-up measures in the control group due to protocol requirements and the option for patients to crossover. For sham control patients who later crossed over to RDN before their 36-month follow-up (n = 13), the last measure prior to RDN was imputed at 36 months. Results: Long-term, 36-month safety and efficacy outcomes of the first 80 patients andomised 1:1 into the RDN (n = 38) and sham control arms (n = 42) will be presented at ESH 2022, in addition to a time in blood pressure target range analysis. Conclusions: Thirty-six month results evaluating the long-term efficacy and durability of RDN compared to a sham control in SPYRAL HTN-ON MED for patients with uncontrolled hypertension will be presented at ESH 2022.